A closer look at the role of urotensin II in the metabolic syndrome - Barrette, Pierre-Olivier; Giaid Schwertani, Adel (Frontiers in Endocrinology, 2012)
Urotensin II (UII) is a vasoactive peptide that was first discovered in the teleost fish, and later in mammals and humans. UII binds to the G protein coupled receptor GPR14 (now known as UT). UII mediates important physiological and pathological actions by interacting with its receptor. The metabolic syndrome (MetS) is described as cluster of factors such as obesity, dyslipidemia, hypertension and insulin resistance, further leading to development of type 2 diabetes mellitus and cardiovascular diseases. UII levels are upregulated in patients with the MetS. Evidence directly implicating UII in every risk factor of the MetS has been accumulated. The mechanism that links the different aspects of the MetS relies primarily on insulin resistance and inflammation. By directly modulating both of these factors, UII is thought to play a central role in the pathogenesis of the MetS. Moreover, UII also plays an important role in hypertension and hyperlipidemia thereby contributing to cardiovascular complications associated with the MetS.